PENGARUH OWNERSHIP STRUCTURE DAN INTELLECTUAL CAPITAL DISCLOSURE TERHADAP PROFITABILITY - Livia Febrina; Saarce Elsye Hatane (Business Accounting Review, 2018)
This research aimed to know the affect of ownership structure and intellectual capital disclosure. Sample used consisted of 42 banking companies listed in the Indonesia Stock Exchange with observation years during 2010-2016. Data processed using WarpPLS software version 5.0.The results of the study found positive influence of government ownership on intellectual capital disclosure. Positive influence of foreign institutional ownership on intellectual capital disclosure. Influence of intellectual capital disclosure to profitability, positive influence of government ownership on profitability, and the positive influence of foreign institutional ownership on profitability. Intellectual capital disclosure failed to mediate the influence of  ownership structure on profitability.